A history of the expansion of Christianity ; v. 6 the great century in Northern Africa and Asia A.D. 1800-A.D. 1914 - Latourette, Kenneth Scott 1884-1968 (Exeter, UK Paternoster, 1971)
Includes bibliographical references and index.
First published 1944, Harper and Row, Publishers, New York.
Keywords: Church history -- 19th century -- Asia; Church history -- 19th century -- missionary activity